Outcome and Prognostic Indicators of Patients with Hematopoietic Stem Cell Transplants Admitted to the Intensive Care Unit. (13th August 2009) - Huynh, Thanh N.; Weigt, S. Sam; Belperio, John A.; Territo, Mary; Keane, Michael P.
Abstract : The prognosis of patients with hematopoietic stem cell transplants (HSCTs) who require admission to the intensive care unit (ICU) has been regarded as extremely poor. We sought to re-evaluate recent outcomes and predictive factors in a retrospective cohort study. Among the 605 adult patients that received an HSCT between 2001 and 2006, 154 required admission to the ICU. Of these, 47% were discharged from the ICU, 36% were discharged from the hospital, and 19% survived 6 months. Allogeneic transplant, mechanical ventilation, vasopressor-use, and neutropenia were each associated with increased mortality, and the mortality of patients with all four characteristics was 100%. Hemodialysis was also associated with increased mortality in a Kaplan-Meier analysis but did not appear important in a multivariate tree analysis. A final Cox model confirmed that allogeneic transplant, mechanical ventilation, and vasopressor-use were each independent risk factors for mortality in the 6 months following ICU admission.